Analysis of the Du Pont System to Assess the Financial Performance of Property and Real Estate Subsector Companies Listed on the Indonesia Stock Exchange for the 2020–2024 Period - Kartika Wulandari; Renny Renny (Asosiasi Dosen Muda Indonesia, 2026)
Assessing financial performance is essential for determining whether a company is financially healthy and capable of maintaining its business continuity. This study aims to analyze the financial performance of property and real estate subsector companies listed on the Indonesia Stock Exchange during the 2020–2024 period using the Du Pont System. This research employed a quantitative descriptive approach using secondary data obtained from annual financial reports published on the official website of the Indonesia Stock Exchange and the respective companies. The sample was selected using purposive sampling and consisted of four companies, resulting in 20 firm-year observations. Financial performance was evaluated using Net Profit Margin (NPM), Total Asset Turnover (TATO), Return on Investment (ROI), Equity Multiplier (EM), and Return on Equity (ROE). The data were analyzed through descriptive analysis and multiple linear regression using SPSS. The results indicate that the financial performance of the sampled companies fluctuated throughout the study period, with each company demonstrating different strengths in profitability, asset utilization, capital structure, and equity returns. Partially, NPM, TATO, and ROI significantly affected ROE, whereas EM had no significant effect on ROE. Simultaneously, NPM, TATO, ROI, and EM significantly affected ROE. These findings indicate that corporate financial performance is more strongly influenced by profitability and asset utilization efficiency than by capital structure.